Peningkatan Pemahaman Konsep Grafik Fungsi Trigonometri Siswa SMK melalui Penemuan Terbimbing Berbantuan Software Autograph - Sahat Saragih; Vira Afriati (Jurnal Pendidikan dan Kebudayaan, 2012)
This research is aimed to know 1) if the increase of student’s conceptual understanding on trigonometric function graph through guided inquiry using Autograph software is greater than those with usual approach, 2) how the student’s mastery in learning and student’s learning activity are. This is an experimental research conducted in SMK Telkom Sandhy Putra and SMK Sandhy Putra II Medan (tourism group) with the population are all the students in grade XI of the schools and two classes from each school were randomly taken as samples. t – test is applied to analyze the normalized gain of students’ conceptual understanding. The research shows that the increase of student’s conceptual understanding on trigonometric function graph through guided inquiry using Autograph software is greater than those with usual approach, 2)the mastery in learning and learning activity of students implementing guided inquiry using Autograph is greater than those with usual approach So, teachers should apply guided inquiry approach using Autograph as one of learning approach alternatives. ABSTRAK Penelitian ini bertujuan untuk mengetahui: 1) apakah peningkatan pemahaman konsep siswa pada grafik fungsi trigonometri dengan penemuan terbimbing berbantuan Software Autograph lebih tinggi daripada siswa yang diberi pendekatan biasa; dan 2) bagaimana ketuntasan dan aktivitas belajar siswa dengan penemuan terbimbing berbantuan Software Autograph. Penelitian ini merupakan studi eksperimen di SMK Telkom Sandhy Putra dan SMK Sandhy Putra II Medan (Kelompok Pariwisata) dengan mengambil sampel 2 kelas dari masing masing sekolah secara acak. Data yang diperoleh secara ternormalisasi dinalisis dengan menggunakan uji t. Hasil penelitian menunjukkan bahwa: 1) peningkatan pemahaman konsep siswa pada grafik fungsi trigonometri yang memperoleh pendekatan penemuan terbimbing berbantuan Software Autograph lebih tinggi dari siswa yang memperoleh pendekatan biasa; dan 2) ketuntasan dan aktivitas belajar siswa yang memperoleh pendekatan penemuan terbimbing berbantuan Software Autograph lebih tinggi dari siswa yang memperoleh pendekatan biasa.